Transformasi Diri Pemelajar BIPA melalui Penulisan Ulang Cerita Rakyat: Pendekatan Hermeneutik terhadap Nilai Budaya dan Karakter - Wahyudi Siswanto; Dwi Sulistyorini; Dewi Ariani; Prima Vidya Asteria; Madiawati Binti Mamat (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Indonesian folktales, as part of the nation’s cultural heritage, contain local wisdom that reflects the worldview and collective values of Indonesian society. In the context of teaching Indonesian to speakers of other languages (BIPA), folktales serve not only as linguistic input but also as pedagogical tools for introducing cultural values and fostering character development among foreign learners. This study aims to examine the forms of self-transformation experienced by BIPA learners through the activity of rewriting Indonesian folktales. A descriptive qualitative approach was employed, grounded in transformative learning theory and hermeneutic analysis. The participants consisted of five advanced-level BIPA learners from Malaysia, South Korea, and China enrolled in a language program at an Indonesian state university. Data were collected through rewritten narrative texts and in-depth interviews, then analyzed hermeneutically through stages of initial comprehension, theme identification, contextual interpretation, and reflection on transformation. The findings reveal that learners experienced personal growth by interpreting cultural values such as livelihood, cooperation, and deliberation, and internalizing character traits such as honesty, responsibility, and respect for others. The act of rewriting served as a reflective process that fostered cross-cultural understanding and cognitive-affective transformation, thereby enriching BIPA learning experiences. This study recommends the integration of folktales as value-based and culturally grounded learning materials in BIPA instruction.